(untitled) (Baghdad Science Journal, 2023)
The aim of this research is to employ starch as a stabilizing and reducing agent in the production of CdS nanoparticles with less environmental risk, easy scaling, stability, economical feasibility, and suitability for large-scale production. Nanoparticles of CdS have been successfully produced by employing starch as a reducing agent in a simple green synthesis technique and then doped with Sn in certain proportions (1%, 2%, 3%, 4%, and 5%).According to the XRD data, the samples were crystallized in a hexagonal pattern, because the average crystal size of pure CdS is 5.6nm and fluctuates in response to the changes in doping concentration 1, 2, 3, 4, 5 %wt Sn, to become 4.8, 3.9, 11.5, 13.1, 9.3 nm respectively. An increase in crystalline size has been noticed in the doped CdS than in the pure CdS. The particle size is within the range of 24-103 nm, according to SEM data from pure CdS and of the doped with Sn particles. The band gap’s energy values, according to UV-Vis reflection spectroscopy were 3.06,2.61 ,2.63, 2.63, 2.66,2.69 eV for pure and doped with Sn 1%, 2%, 3%, 4%, 5% respectively. The grain size and roughness rate of pure CdS materials and doped with Sn are shown in AFM results 2.16,2.39,10.07,11.33, 12.47,18.56 nm and average diameter is 30.15, 11.71, 66.06, 48.27,82.011, 80.35 nm for pure and doped with tin 1%, 2%, 3%, 4%, 5% respectively.